Critical Success Factors of Public Private Partnership in Hydropower Sector of Nepal - Gautam, Chintamani (PYC Nepal Journal of Management, 2017)
This paper aims to identify the Critical Success Factors (CSFs) of Public Private Partnership (PPP) in hydropower secter of Nepal. The study was based on a survey of 141 experts and practitioners involved in private and public hydropower projects. The study revealed that project technical feasibility, favorable legal framework, good governance, transparent procurement process and macro-economic stability were identified as most CSFs of PPPs. The comparative analysis of rank, found that among the 21 CSFs, four factors: macro-economic condition, employment opportunities, government’s technical support and government’s managerial support were considered equally important CSFs by the public and private sector respondents. It is concluded that for the success of PPPs in hydropower sector, the concerned authorities should use private sector more efficiently, specially for the technical support and government for devising favorable legal framework for the PPP projects. This study offers some insights on CSFs for policy makers concerning the successful implementation of PPPs in hydropower sector. Key Words: Public private partnership, Hydropower sector, Critical success factors. Mr. Gautam is Lecturer at Public Youth Campus, Tribhuvan University.